Teatro do oprimido: implicações metodológicas para a educação de adultos - Waldimir Rodrigues Viana (2011)
This paper we are presenting results from the development and respective analysis of a proposal of the Theater of the Oppressed with adult students from EJA (adults and young people education). The field research lasted a school semester. The works were performed with 27 students of the Primary Education Project (PROEF II - second segment Education of Young People and Adults Project), which operates in the Pedagogical Center of the Federal University of Minas Gerais. This paper is divided into six chapters. The first chapter introduces the researcher and his motivations. We then go through a brief background synthesis of the education of young people and adults in Brazil. Also in this initial part we present the methodological configuration, the quests of the research and the general text organization with the aim to guide the reader in relation to the content. In the second chapter a historical overview of the theater development is outlined with the intention of debating the TO (Theater of the Oppressed) under the education perspective. We take the eastern and western drama as reference. Thus it is possible to perceive the differential of the Theater of the Oppressed in relation to other theatrical poetics, precisely due to its political and pedagogical function which we consider very significant and relevant to the EJA context.Next we dedicate a chapter to the closeness between Paulo Freires Pedagogy of the Oppressed and Augusto Boals Theatre of the Oppressed. The fourth chapter in its turn is the general explanation about what we observed and what was constructed by the subjects in the research field. Whereas the fifth chapter is dedicated to the final considerations. In the sixth chapter we summarize and present our conclusions that the TO, dispensing rigid technical development, even without refuting the organization and scenic beauty, valuing the criticality and real life themes, it provides all EJA students with means to create and act dramatically